MG-108 Agenesis of the corpus callosum and autism associated with zeb1 gene deletion – a case report. (4th December 2015) - Inbar-Feigenberg, Michal; Chung, Brian HY; Marshall, Christian R; Merico, Daniele; Stavropoulos, D James; Chitayat, David
Abstract : Background: Agenesis of the corpus callosum (ACC) is a rare congenital anomaly presenting with partial or complete absence of the corpus callosum (CC). ACC could present as an isolated finding or a part of a genetic syndrome. A recent publication reported two cases of mal-development of CC in two unrelated individuals with posterior polymorphous corneal dystrophy (PPCD), an autosomal dominant inherited disorder of the corneal endothelium. Both cases presented novel deletions of the ZEB1 gene. *ZEB1 mutations are reported in approximately one third of PPCD patients. Objective: To report a case of a child with ACC and de novo chromosome 10 deletion involving ZEB1 gene. Case report: a 12-year-old girl presented with facial dysmorphism, bilateral renal reflux, developmental delay, autism and ACC. She presented with normal growth parameters, continued to acquire new developmental skills with no regression episodes or seizures. Ophthalmological exam showed thinning of the retinal nerve fibre layer in the nasal aspect around the discs with relative sparing of the macular areas bilaterally. The rest of the ocular examination, including corneal exam was normal. Results: Whole genome sequencing revealed heterozygous de novo deletion in chromosome 10p11.23- p11.22 (del:chr10:30814000–32892000) overlapping ZEB1 gene. Conclusion: This is the third case reported of ZEB1 gene deletion in a patient with CC anomalies, and the first patient with no corneal anomalies but with autism. This finding might imply a broader phenotypic range for ZEB1 deletion than previously thought and add it to the possible causes of autism.